2017
DOI: 10.1002/chem.201704124
|View full text |Cite
|
Sign up to set email alerts
|

A Rotaxane Scaffold for the Construction of Multiporphyrinic Light‐Harvesting Devices

Abstract: As ophisticated photoactive molecular device has been prepared by combiningr ecent conceptsf or the preparation of multifunctional nanomolecules (click chemistry on multifunctional scaffolds) with supramolecular chemistry (self-assembly to prepare rotaxanes). Specifically,aclickable [2]rotaxane scaffold incorporating af ree-base porphyrin stopperh as been prepared and functionalized with ten peripheralZ n(II)-porphyrinm oieties. Electrochemical investigations of the final compound revealed ap eculiar behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 91 publications
0
27
0
1
Order By: Relevance
“…The ability of 6a to form inclusion complexes with compound 7 was investigated by 1 H‐NMR binding studies in CDCl 3 at 25 °C ( Figure ). Successive additions of host 6a to a CDCl 3 solution of 7 led to continuous changes in the chemical shift of the signals of the guest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of 6a to form inclusion complexes with compound 7 was investigated by 1 H‐NMR binding studies in CDCl 3 at 25 °C ( Figure ). Successive additions of host 6a to a CDCl 3 solution of 7 led to continuous changes in the chemical shift of the signals of the guest.…”
Section: Resultsmentioning
confidence: 99%
“…Rotaxane 9 was obtained by reaction of a mixture of 6a and 7 with acyl chloride 8 . The concentration and temperature conditions were adapted to favor the assembly of the pseudo‐rotaxane intermediate from 6a and 7 as recently described for related rotaxanes prepared from 7 . Under these conditions, rotaxane 9 was obtained in 54% yield.…”
Section: Resultsmentioning
confidence: 99%
“…As a step towards more efficient light harvesting arrays, Delavaux‐Nicot, Maisonhaute, and Nierengarten et al have recently reported the synthesis of a [2]rotaxane structure 19 comprising a macrocycle with ten pendant zinc(II) porphyrins attached, and a central rotaxane thread with a free‐base porphyrin stopper (Figure ) . The [2]rotaxane core was first synthesized using known directed synthesis techniques and the ten pendant zinc(II) porphyrin units were then covalently attached to the macrocycle by copper(I) catalyzed triazole click chemistry.…”
Section: Rotaxanes With Porphyrins Embedded Within the Macrocycle mentioning
confidence: 99%
“…Light harvesting molecular device 20(Zn 10 )(H 2 ) constructed on a rotaxane scaffold and model compound 21H 2 . Adapted from ref …”
Section: Weak Intramolecular Interactions To Control the Conformatmentioning
confidence: 99%
“…(C) Schematic representation of the photoinduced energy transfer, the calculated structure of 20(Zn 10 )(H 2 ) used for the illustration has a partially folded macrocyclic component illustrating how the distances between the peripheral Zn(II)‐porphyrin units and the free‐base porphyrin of the axle can be influenced by the intramolecular coordination of the metallated porphyrins with triazole linkers (C: green for the axle unit in space‐filling and gray for the pillar[5]arene moiety in ball and stick, N: blue, O: red, F: pale green, Zn: pink, H: white). Adapted from ref …”
Section: Weak Intramolecular Interactions To Control the Conformatmentioning
confidence: 99%